Structure/function analyses indicate novel roles for mycobacterial DnaQ homologs in genome maintenance - Griffault, Dimitri (Department of Pathology, 2025)
Mycobacterial DNA metabolism is of increasing interest as both an underexplored source of new targets for anti-tuberculosis (TB) drug development and for its potential role in the emergence of drug-resistant Mycobacterium tuberculosis strains. However, the redundancy implied by the sizable complement of DNA replication and repair pathways complicates investigations of gene function. There are, moreover, multiple examples in mycobacteria of apparent fusion – or hybrid – proteins in which N-and C-terminal domains appear to provide discrete functions. Both challenges apply to the mycobacterial DnaQ homologs – comprising separate DnaQ and DnaQ-UvrC hybrid proteins – which, by analogy to model organisms such as E. coli, have traditionally been assumed to fulfil proofreading roles in DNA replication owing to the presence of conserved exonuclease domains. Phylogenetic analysis of DnaQ-like proteins revealed a unique domain composition specific to the Mycobacterium genus comprising a conserved BRCA1 C Terminus (BRCT) domain in DnaQ. Owing to the presence of the BRCT domain and based on the phenotypes observed in domain-targeted mutants, it appeared that the activity of DnaQ protein (M. tuberculosis Rv3711c; M. smegmatis MSMEG_6275) might be linked to the mycobacterial gyrases that are responsible for DNA negative supercoiling following replication. The phylogenetic analysis also revealed highly conserved nucleotide excision repair (NER) proteins among bacteria; however, some species like Actinobacteria, possess both a canonical UvrC along with a DnaQ-UvrC protein. The mycobacterial DnaQ-UvrC (M. tuberculosis Rv2191; M. smegmatis MSMEG_4259) N- terminal was shown to be structurally very similar to that of DnaQ and its C-terminal to that of UvrC, giving the ability to bind either the β-clamp or the components of the UvrABC system. Opposing phenotypes between DnaQ-UvrC (M. tuberculosis Rv2191; M. smegmatis MSMEG_4259) and uvrC deletion imply a DNA-damage specific NER in mycobacteria. This was further confirmed using a combination of gene knockout, site-directed mutants and CRISPRi of NER genes, namely uvrB and uvrC, in DNA damaging conditions. However, further work is required to elucidate the precise functions of DnaQ and DnaQ-UvrC, and their contribution to genome dynamics in a family of organisms that includes major human and animal pathogens.